SOME ASPECTS OF THE ACCOUNTING OF TAX PAYMENTS IN COMMERCIAL BANKS - Sherimbetov Inomjon Khalilullayevich,; Mukhammadiyeva Gulnora Jumanazarovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines tax payments paid by commercial banks and their accounting and tax accounting issues.